Mengatasi Genangan Jalan Donowati Kota Surabaya Melalui Perbaikan Drainase - Jenny Caroline; Arintha Indah Dwi Syafiarti (Kadiri University, 2023)
Surabaya plays a crucial role as the economic center in eastern Indonesia. However, it is identified as a waterlogging-prone area. Several regions have experienced flooding with water heights ranging from 10 to 70 cm, lasting up to 6 hours. This issue also happened in the Donowati area, Surabaya where mismatches in the construction of urban drainage channels with design criteria were found, resulting in inundation. These inundations cause infrastructure damage, health risks, disruption of activities, and economic losses. This research aims to evaluate and optimize the drainage system in Jalan Donowati, Surabaya. The research was conducted by collecting existing canal dimension data and hydrological data. Furthermore, data analysis was carried out, including hydrological and hydraulics analysis. Repairs will be carried out if an overflow occurs so the channel can run normally. The results showed drainage channels on Jalan Donowati could not accommodate rainwater due to their small capacity, namely one secondary and three tertiary channels. The channel redesign obtained dimensions of 1 m x 1 m for the secondary channel and 0.7 m x 0.6 m for the tertiary channel. The validation results show that the new dimension is safe against high rainfall. In addition to channel re-dimensions, inlet additions were also made to allow rainwater to enter the drainage canals more efficiently. So that with this new dimension, it can prevent inundation that occurs during the rainy season.